The Role of Spiritual Intelligence in EFL Teachers’ Pedagogical Success: An Explanatory Sequential Mixed-Methods Study in a Technology-Rich Context - Hossein Isaee (CV Media Inti Teknologi, 2026)
Background: Growing digitalization in education has renewed interest in human-centered capacities that support effective teaching in increasingly technology-rich learning environments. Among these, spiritual intelligence (SI) has attracted attention as a multidimensional construct associated with meaning-making, self-awareness, ethical sensitivity, and emotional regulation. However, limited empirical evidence exists regarding its relationship with pedagogical success among English as a Foreign Language (EFL) teachers. Aims: This study aimed to investigate the relationship between EFL teachers’ spiritual intelligence and pedagogical success, examine the predictive contribution of SI dimensions, and explore how spiritual intelligence is reflected in teachers’ professional practice. Methods: A mixed-methods design was employed. Quantitative data were collected from 120 EFL teachers using validated measures of SI and pedagogical success and analyzed through descriptive statistics, correlation, and multiple regression analyses. Qualitative data were obtained through interviews, classroom observations, and syllabus analysis. Results: The findings revealed a strong positive relationship between overall SI and pedagogical success. Transcendent self-realization emerged as the strongest predictor, followed by patience and spiritual experience. Qualitative findings indicated that teachers with higher levels of SI demonstrated stronger interpersonal relationships, greater emotional resilience, enhanced self-awareness, a stronger sense of purpose, and higher levels of professional commitment. Conclusion: SI appears to be meaningfully associated with effective teaching and may represent an important personal resource for EFL educators. The study contributes to discussions of teacher effectiveness and holistic professional development while highlighting the continuing importance of human-centered capacities in contemporary educational environments.